Severe Streptococcus equi Subspecies zooepidemicus Outbreak from Unpasteurized Dairy Product Consumption, Italy - Serena Bosica; Alexandra Chiaverini; Maria Elisabetta De Angelis; Antonio Petrini; Daniela Averaimo; Michele Martino; Marco Rulli; Maria Antonietta Saletti; Maria Chiara Cantelmi; Franco Ruggeri; Fabrizio Lodi; Paolo Calistri; et al. (Emerging Infectious Diseases, 2023)
During November 2021–May 2022, we identified 37 clinical cases of Streptococcus equi subspecies zooepidemicus infections in central Italy. Epidemiologic investigations and whole-genome sequencing showed unpasteurized fresh dairy products were the outbreak source. Early diagnosis by using sequencing technology prevented the spread of life-threatening S. equi subsp. zooepidemicus infections.